Influence of radiopacifying agents on the solubility, pH and antimicrobial activity of Portland cement - Weckwerth, Paulo Henrique; MacHado, Adriano Cosme de Oliveira; Kuga, Milton Carlos [UNESP]; Vivan, Rodrigo Ricci; Polleto, Raquel da Silva; Duarte, Marco Antonio Hungaro (FapUNIFESP (SciELO), 2012)
The aim of this study was to evaluate the interference of the radiopacifiers bismuth oxide (BO), bismuth carbonate (BC), bismuth subnitrate (BS), and zirconiun oxide (ZO) on the solubility, alkalinity and antimicrobial properties of white Portland cement (WPC). The substances were incorporated to PC, at a ratio of 1:4 (v/v) and subjected to a solubility test. To evaluate the pH, the cements were inserted into retrograde cavities prepared in simulated acrylic teeth and immediately immersed in deionized water. The pH of the solution was measured at 3, 24, 72 and 168 h. The antimicrobial activity was evaluated by a radial diffusion method against the microorganisms S. aureus (ATCC 25923), P. aeruginosa (ATCC 27853), E. faecalis (ATCC 29212) and C. albicans (ATCC 10231). The zone of microbial growth inhibition was measured after 24 h. The addition of BS and BC increased the solubility of the cement. The pH values demonstrated that all materials produced alkaline levels. At 3 h, BS showed lower pH than WPC (p<0.05). At 168 h, all materials showed similar pHs (p>0.05). The materials did not present antimicrobial activity for S. aureus, P. aeruginosas and E. faecalis (p>0.05). With regards to C. albicans, all materials formed an inhibition zone, mainly the mixture of WPC with ZO (p<0.05). The type of radiopacifier incorporated into WPC interfered with its physical and antimicrobial properties. ZO was found to be a viable radiopacifier that can be used with WPC.
Keywords: Antimicrobial activity; pH; Portland cement; Radiopacifier